Internet connectivity disruption in Albania (Albania) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Albania. Data sourced from IODA.
Network Disruption Incident ID: AL-2026-0007. Severity: critical. Confidence: 65%